2017
DOI: 10.1242/dev.146050
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of VEGF-inducible genes by an ERK-ERG-p300 transcriptional network

Abstract: The transcriptional pathways activated downstream of vascular endothelial growth factor (VEGF) signaling during angiogenesis remain incompletely characterized. By assessing the signals responsible for induction of the Notch ligand delta-like 4 (DLL4) in endothelial cells, we find that activation of the MAPK/ERK pathway mirrors the rapid and dynamic induction of DLL4 transcription and that this pathway is required for DLL4 expression. Furthermore, VEGF/ERK signaling induces phosphorylation and activation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 80 publications
5
73
1
Order By: Relevance
“…As shown in Figure S5D-S5G, DAPT treatment abrogated the enhancing effect of LY294002 on formation of DLL4 + CXCR4 +/− arterial HE and CD235a/CD41a − CD45 + multipotential hematopoietic progenitors, consistent with prior observations in the mouse system that MAPK pathway specifies arterial identity of non-HE through activation of NOTCH signaling (Wythe et al, 2013). It has also been demonstrated that MAPK/ERK pathway promotes phosphorylation of ETS1 and ETS2 (Petrovic et al, 2003; Yang et al, 1996) and other ETS factor members including ELK1 (Yang et al, 1998) and ERG (Fish et al, 2017). ERG phosphorylation is required for p300 recruitment to DLL4 arterial-specific enhancer and its activation (Fish et al, 2017; Wythe et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure S5D-S5G, DAPT treatment abrogated the enhancing effect of LY294002 on formation of DLL4 + CXCR4 +/− arterial HE and CD235a/CD41a − CD45 + multipotential hematopoietic progenitors, consistent with prior observations in the mouse system that MAPK pathway specifies arterial identity of non-HE through activation of NOTCH signaling (Wythe et al, 2013). It has also been demonstrated that MAPK/ERK pathway promotes phosphorylation of ETS1 and ETS2 (Petrovic et al, 2003; Yang et al, 1996) and other ETS factor members including ELK1 (Yang et al, 1998) and ERG (Fish et al, 2017). ERG phosphorylation is required for p300 recruitment to DLL4 arterial-specific enhancer and its activation (Fish et al, 2017; Wythe et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been demonstrated that MAPK/ERK pathway promotes phosphorylation of ETS1 and ETS2 (Petrovic et al, 2003; Yang et al, 1996) and other ETS factor members including ELK1 (Yang et al, 1998) and ERG (Fish et al, 2017). ERG phosphorylation is required for p300 recruitment to DLL4 arterial-specific enhancer and its activation (Fish et al, 2017; Wythe et al, 2013). To determine, whether ETS1 activity in our system is controlled by MAPK/ERK signaling, we assessed how ERK inhibition affects HE specification and hematopoietic differentiation in the presence of DOX (Figure S6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, animal models carrying mutations in components of the Vegf pathway showed simultaneous defects in EC proliferation and migration. For instance, zebrafish mutants in kdrl, plcg or treated with the Vegf pathway inhibitor SU5416 display an absence of ERK phosphorylation (Fish et al, 2017; Shin et al, 2016), together with a reduction in ISV outgrowth and cell numbers. Similarly, mutants in vegfaa show a severe reduction in EC numbers and migration during ISV formation (Jin et al, 2017), phenotypes also seen in VEGFA mutant mice (Carmeliet et al, 1996; Ferrara et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…To support in silico observations we expanded upon our previous transcriptomic study [30] to identify putative positive-feedback regulators of Vegfr by defining genes transcriptionally activated by Vegfr and repressed by Notch signaling in zebrafish ECs (Figure 2A). Of only 10 candidate Vegfr/Notch-regulated transcripts we identified h2.0-like homeobox-1 (hlx1), a known transcriptional target of Vegfr activity in-vivo [30][31][32] and the atypical tetraspanin transmembrane 4 L6 family member 18 (tm4sf18). TM4SF family proteins are known membrane-associated adaptors that ligand-independently activate receptor tyrosine kinase activity [33,34].…”
Section: Vegfr-induced Expression Of Tm4sf18 Promotes Positive-feedbackmentioning
confidence: 99%